2007
DOI: 10.1007/s11144-007-5176-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of aluminum powder oxidation by water at 100°C

Abstract: The kinetics of aluminum powder oxidation by water at 100°С has been investigated using three types of aluminum powders. A "shrinking sphere" model was used for description of the experimental data at the initial reaction stage, whereas a "parabolic" diffusion equation was used at the second stage. Variation of the specific reactivity is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Meanwhile, the rates of Al consumption at the second diffusion-controlled stage of hydrothermal oxidation were substantially different. For ASD-4 this rate was higher by two orders of magnitude (Tikhov et al, 2007). Therefore, the smallest hydroxide (oxide) particles were obtained for this PPM.…”
Section: Metal Ceramic and Polymeric Composites For Various Uses 202mentioning
confidence: 77%
See 1 more Smart Citation
“…Meanwhile, the rates of Al consumption at the second diffusion-controlled stage of hydrothermal oxidation were substantially different. For ASD-4 this rate was higher by two orders of magnitude (Tikhov et al, 2007). Therefore, the smallest hydroxide (oxide) particles were obtained for this PPM.…”
Section: Metal Ceramic and Polymeric Composites For Various Uses 202mentioning
confidence: 77%
“…Quantitative estimates of the oxide content based on the earlier reported calibration curve (Tikhov et al, 2004) are shown in Table 1. The differences of the oxide content in cermets are mostly due to different reactivity of the used aluminum powders at the initial hydrothermal oxidation stage (Tikhov et al, 2007). Aluminum is practically not subjected to any oxidation during calcination in air at 550°C.…”
Section: Phase Composition Of Al 2 O 3 /Al Compositesmentioning
confidence: 99%
“…There are many reports of systems that behave like the Yagi model and different modifications to this model have been proposed. It has been used to explain solid-liquid reactions under non-isothermal conditions [12], when the nucleus is porous [13,14], for different reaction orders [12], and considering a parabolic equation for the diffusion stage [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the study [16], a first-order reaction model was used to approximate kinetic curves for aluminum powder, casing, and foil reacting with water under hydrothermal conditions. For commercial Al powders ('ASD-1', 'ASD-4', and 'PAP-2' grades) reacting with water at 100 • C, a 'shrinking sphere' equation was found to be applicable to the kinetics description at the initial stage, and the second stage was approximated using the parabolic diffusion equation [45]. For Al powder reacting with Na 2 SnO 3 (0.05 M), a similar 'shrinking sphere' model was used at the first stage, and the Ginstling-Brounshtein equation was employed for the second one [46].…”
Section: Introductionmentioning
confidence: 99%